HYDROCHEMISTRY AND MOBILIZATION OF GOLD IN THE HYPERGENESIS ZONE (KUZNETSK ALATAU, RUSSIA) - Shvartsev S.L.; Dutova E.M. (My University, 2001)
Based on the results of the geochemical study of groundwater from the Central ore field (Kuznetsk Alatau) and of the distribution of gold in the latter, the mechanism of mobilization, migration, and concentration of this element under conditions of the mountainous-forest landscape is outlined. Physicochemical modeling and thermodynamic calculations indicate that the water-rock system is of the equilibrium-disequilibrium type, which provides continuous incongruent dissolution of major minerals accompanied by the formation of kaolinite and, less commonly, of montmorillonite and hydromicas. As a result, most elements transferred into dissolution (70.6%) form the secondary mineral phase, while their minor part (29,4%) is concentrated in the solution. Because of the disequilibrium system, the amount of elements in the solution grows as the time of water-rock interaction increases. A similar behavior is also characteristic of gold, 63.0% of which is fixed by forming secondary compounds and 37.0% is concentrated in the aqueous solution. The obtained results elucidate the mechanism of dissolution, migration, and concentration of gold in the solution, which indicates that gold mobilization occurs in the process of incongruent aluminosilicate dissolution, pyrite oxidation, and partial dissolution of gold grains. Gold that was entrapped by the aqueous solution is concentrated in the latter and forms, reaching an equilibrium, a native phase in certain geochemical environments or at geochemical barriers. It is shown that gold mobilization is only one part of a more general ore-generating process that is peculiar to the water-rock system as a whole.